Distribution of household assets in Croatia (Public Sector Economics - submission site, 2020)
This paper analyses the main components and distribution of household net assets in Croatia on the basis of the data from the Household Finance and Consumption Survey (HFCS) by taking into account different socio-demographic characteris¬tics of households. The main results indicate that real assets are widely distributed among households, whereby 85% of households own the household main resi¬dence. Financial assets and liabilities account for larger share among wealthier households. The analysis of the main determinants establishing the position of an individual household in distribution of assets has additionally highlighted the importance of the household main residence (HMR). Households with inherited HMR are less likely to be positioned in the lowest net asset quintile. In addition, households with HMR in the city of Zagreb or on the Adriatic Coast are more likely to be in higher asset quintile groups.